Cenozoic tectonics and landform evolution in the Qilian Mountains and adjacent areas. Issue 5 (23rd March 2020) - Du, Kai; Yang, Lirong; Zhang, Rui; Yue, Leping; Guo, Huaijun; Zhang, Yunxiang; Li, Jianxing; Gong, Hujun
ABSTRACT: The formation of the Qilian mountains and the evolution of adjacent basins were controlled by the uplift and northeastward growth of the Tibetan Plateau. In a field survey conducted on the main Cenozoic basin sediments in the Qilian Mountains and adjacent areas, fission track age data of apatite obtained previously were analyzed. Cenozoic tectonics and landform evolution in the area where the Qilian Mountains now stand and its response to the uplift of the Tibetan Plateau were studied. In the Oligocene Epoch, the Tibetan Plateau was initially uplifted and extended northeastward, forming the Guide-Xining-Lanzhou-Linxia foreland basin on the northern margin of the western Qinling Mountains, and the foreland basin in the area where the Qilian Mountains now stand received widespread sediments. In the Miocene, influenced by the enhanced uplift and northeastward thrust of the Tibetan Plateau, a stage of intracontinental squeezing orogeny and foreland basin splitting began in the area where the Qilian Mountains now stand. In the Pliocene Epoch, the Qilian Mountains were continuously uplifted, the basins shrank, large lake basins disappeared gradually, and large-area red-clay-type aeolian sediments appeared. During the Quaternary Period, the uplift of the Tibetan Plateau accelerated, causing a rapid rise in the altitude of the Qilian Mountains. Global climate change occurred and mountain glaciers began to develop. Quaternary moraine deposits appeared for the first time in the area, and very thick loess sediments appeared in the Longzhong area, east of the area where the Qilian Mountains now stand, forming the famous Loess Plateau.